In vivo tissue engineering of an adipose tissue flap using fat grafts and Adipogel. (8th March 2020) - Debels, Heidi; Palmer, Jason; Han, Xiao‐Lian; Poon, Christopher; Abberton, Keren; Morrison, Wayne
Abstract: For decades, plastic surgeons have spent considerable effort exploring anatomical regions for free flap design. More recently, tissue‐engineering approaches have been utilised in an attempt to grow transplantable tissue flaps in vivo. The aim of this study was to engineer a fat flap with a vascular pedicle by combining autologous fat grafts and a novel acellular hydrogel (Adipogel) in an established tissue‐engineering model comprising a chamber and blood vessel loop. An arteriovenous loop was created in the rat groin from the femoral vessels and positioned inside a perforated polycarbonate chamber. In Group 1, the chamber contained minced, centrifuged autologous fat; in Group 2, Adipogel was added to the graft; and in Group 3, Adipogel alone was used. Constructs were histologically examined at 6 and 12 weeks. In all groups, new tissue was generated. Adipocytes, although appearing viable in the graft at the time of insertion, were predominantly nonviable at 6 weeks. However, by 12 weeks, new fat had formed in all groups and was significantly greater in the combined fat/Adipogel group. No significant difference was seen in final construct total volume or construct neovascularisation between the groups. This study demonstrated that a pedicled adipose flap can be generated in rats by combining a blood vessel loop, an adipogenic hydrogel, and a lipoaspirate equivalent. Success appears to be based on adipogenesis rather than on adipocyte survival, and consistent with our previous work, this adipogenesis occurred subsequent to graft death and remodelling. The regenerative process was significantly enhanced in the presence of Adipogel.